PENGARUH PENANGANAN KELUHAN (COMPLAINT HANDLING) TERHADAP KEPERCAYAAN DAN KOMITMEN MAHASISWA PADA PERGURUAN TINGGI SWASTA DI BANDAR LAMPUNG - Susi Indriyani; Selvy Mardiana (Jurnal Bisnis Darmajaya, 2016)
The complaint provided by the customer in the use of the product or service is a feedback on the quality of products or services used by customers. The more complaints provided by the customer requires extra attention for any company that received complaints for repair in the manufacture of products or services. Student complaints with the service provided is important because increased revenues resulted in the displacement of students getting higher. Fakor physical evidence (X1), reliability (X2), responsiveness (X3), assurance (X4) and empathy (X5) in the handling of complaints is important that students feel the complaint was well received. Trust and commitment to student education service users to be very important to maintain the image of universities in society.Services in education is an essential element for the creation of a conducive academic atmosphere for the implementation of a successful learning process. In educational institutions excellent service to students is one of the factors that need to be considered well to maintain smooth student study. The purpose of this study to find out how how empathy psychological influence on the trust and commitment of students with explanatory research method by conducting a survey to students in private universities in Bandar Lampung.Results from this study is the physical evidence (X1), reliability (X2), responsiveness (X3), assurance (X4) and empathy (X5) have positive influence and significant impact on the trust and commitment of students, which is given by the supervisor of academic, education personnel, as well as other lecturers provide confidence and commitment to the students that the complaint was handled well and menndapatkan appropriate solutions. The most dominant variable is a variable that affects empathy.Keywords: Complaints, Confidence, Commitment